1995
DOI: 10.1105/tpc.7.11.1933
|View full text |Cite
|
Sign up to set email alerts
|

Two NADPH:Protochlorophyllide Oxidoreductases in Barley: Evidence for the Selective Disappearance of PORA during the Light-Induced Greening of Etiolated Seedlings.

Abstract: Chlorophyll synthesis in barley is controlled by two different light-dependent NADPH:protochlorophyllide oxidoreductases, termed PORA and PORB. PORA is present abundantly in etioplasts but selectively disappears soon after the beginning of illumination. This negative light effect is mediated simultaneously at three different levels. First, the concentration of porA mRNA declines drastically during illumination of dark-grown seedlings. Second, the plastids' ability to import the precursor of PORA (pPORA) is red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 31 publications
4
70
0
Order By: Relevance
“…Unlike PORB mRNA, the accumulation of PORA mRNA is negatively regulated by light (Apel, 1981;Armstrong et al, 1995). This difference in the expression of PORA and PORB has led to the suggestion that PORA's function in etiolated seedlings might be confined to the initial phase of light-induced chloroplast development (Reinbothe et al, 1995a;Sperling et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike PORB mRNA, the accumulation of PORA mRNA is negatively regulated by light (Apel, 1981;Armstrong et al, 1995). This difference in the expression of PORA and PORB has led to the suggestion that PORA's function in etiolated seedlings might be confined to the initial phase of light-induced chloroplast development (Reinbothe et al, 1995a;Sperling et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Mutagenesis and homology modeling studies have provided important insights into the catalytic mechanism of POR (7)(8)(9)(10)(11). All three POR isoforms are nuclear gene products that must be imported posttranslationally into the plastids (12,13). Components have been identified in the plastid envelope mediating this import step (14)(15)(16).…”
mentioning
confidence: 99%
“…In angiosperms such as barley, Arabidopsis (1, 2), tobacco (3) and Amaranthus tricolor (4), and gymnosperms such as pine species (5-7), several por gene families were identified that encode highly conserved POR polypeptides. PORA represents the negatively light-regulated POR enzyme whose level drops as a result of the concerted effect of light at the levels of transcription, mRNA stability, plastid import, and protein degradation after light-induced catalysis (8)(9)(10)(11). PORB, the second POR protein identified in barley and Arabidopsis (1,12), is constitutively expressed in darkgrown, illuminated, and light-adapted plants (see ref.…”
mentioning
confidence: 99%